Interprofessional Health Care Education at Academic Medical Centers: Using a SWOT Analysis to Develop and Implement Programming - David R. Topor; Chandlee Dickey; Laura Stonestreet; Judith Wendt; Adam Woolley; Andrew Budson (Association of American Medical Colleges, 2018)
Introduction Health care is increasingly being provided by interprofessional teams. Academic medical centers (AMCs) need to offer educational experiences for trainees to work on these teams. Few resources exist to guide educational leaders in developing and implementing these experiences to meet the unique needs of their AMC. A commonly used planning tool is the strengths, weaknesses, opportunities, and threats (SWOT) analysis, which can help organizations identify issues and develop strategies that overcome barriers to program implementation. Methods This workshop focuses on teaching participants to use a SWOT analysis to develop interprofessional learning activities. The workshop contains both a didactic component and an experiential component. The workshop was offered as a 60-minute webinar and a 120-minute in-person presentation. The additional hour during the in-person presentation was used for experiential learning activities. Eighty-four educators from a number of health professions attended the webinar, and approximately 50 medical educators attended the in-person presentation. Results Participants reported satisfaction with the workshop and found its content met stated learning objectives. Participants believed they gained both the knowledge to develop a strategic plan to implement interprofessional educational programming and the ability to apply this knowledge at their AMC. Participants reported that their confidence in using strategic planning increased due to workshop participation. Discussion This workshop represents a first step in helping educational leaders learn and use strategies to develop and implement interprofessional educational programming unique to their AMC. This programming is important for training future health care providers to work on interprofessional health care teams.